2017
DOI: 10.1007/s40122-017-0090-5
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Current and Emerging Approaches to Pain Management in the Emergency Department

Abstract: IntroductionPain is the most common symptom prompting an emergency department visit and emergency physicians are responsible for managing both acute pain and acute exacerbations of chronic pain resulting from a broad range of illnesses and injuries. The responsibility to treat must be balanced by the duty to limit harm resulting from analgesics. In recent years, opioid-related adverse effects, including overdose and deaths, have increased dramatically in the USA. In response to the US opioid crisis, emergency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
51
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 61 publications
0
51
0
2
Order By: Relevance
“…One US Emergency Department in particular has been extremely successful in promoting nonopioid management, with a focus on procedural pain management -such as nerve blocks and trigger point injections [9]. Along this line, there is increasing interest among Emergency Physicians to obtain new training and skills to improve pain management in the ED [10].…”
Section: Introductionmentioning
confidence: 99%
“…One US Emergency Department in particular has been extremely successful in promoting nonopioid management, with a focus on procedural pain management -such as nerve blocks and trigger point injections [9]. Along this line, there is increasing interest among Emergency Physicians to obtain new training and skills to improve pain management in the ED [10].…”
Section: Introductionmentioning
confidence: 99%
“…With the update of demand information, enterprises can effectively deal with the mismatch between supply and demand through the multimodal transport logistics supply network, which can reduce inventory backlog and improve customer service level [4][5][6][7][8]. The imbalance of inventory control caused by mismatch between supply and demand can be handled by means of emergency ordering or by multimodal transport from the transshipment center [9][10][11][12][13][14][15]. The problem of emergency ordering is that the adjustment of production resources and the compression of the construction period will inevitably lead to high costs [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, more and more enterprises tend to adopt multimodal transport to deal with the problem of supply and demand mismatch between regions [21]. Previous studies showed the significance of multimodal transport problems [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and solutions [21] that can be improved from different perspectives. For instance, Mengliang et al [1], Todd et al [2], and Pałaszewskatkacz et al [3] showed that demand information cannot be ignored; references [4][5][6][7][8] found the importance of requirements updates; researchers [9][10][11][12][13][14][15] emphasized that safety stock should be considered in multimodal transport; costs control should be considered in multimodal transportation optimization from literatures [16][17][18][19][20]; and Zhang et al [21] provided a good method reference for multimodal transport network optimization problem.…”
Section: Introductionmentioning
confidence: 99%
“…Pain alleviation is a well-established clinical priority in emergency medicine (EM). 1 Recent years have seen ED practice shift towards increased use of non-opioids such as non-steroidal anti-inflammatory drugs (NSAIDs) and paracetamol, which do not have opioids' dependency-related risks. [1][2][3] Diclofenac is an NSAID commonly used in the ED for conditions such as musculoskeletal injury (MSI) and renal colic.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…1 Recent years have seen ED practice shift towards increased use of non-opioids such as non-steroidal anti-inflammatory drugs (NSAIDs) and paracetamol, which do not have opioids' dependency-related risks. [1][2][3] Diclofenac is an NSAID commonly used in the ED for conditions such as musculoskeletal injury (MSI) and renal colic. 4 5 Administered in adult doses ranging from 50 to 100 mg, diclofenac mediates analgesia primarily via inhibition of cyclo-oxygenase-2 (COX-2) enzymatic conversion of arachidonic acid into inflammatory prostaglandins.…”
Section: Introduction Backgroundmentioning
confidence: 99%